Hubungan Antara Iklim Oganisasi Dengan Organizational Citizenship Behavioral (OCB) Pada Perawat RSUD Kabupaten Padang Pariaman - Fisa Amanah (Affection: Journal of Psychology And Counseling, 2024)
Organizational Citizenship Behavior (OCB) is often interpreted as behavior that exceeds formal obligations (extra role) that is not related to direct compensation. The hypothesis proposed is that there is a positive relationship between organizational climate and OCB at RSUD Kab. Padang Pariaman. The subjects of this study were the Children's Room, Inpatient Room, Emergency Room, and Surgery. The sampling technique used in this study was saturated sampling. The research method used a quantitative method with a scale measuring instrument. Data analysis used Product Moment correlation. The number of samples in this study was 30 nurses. The results of the trial showed that the validity coefficient of the Organizational Climate scale moved from rxy = 0.851 to rxy = 0.912, while the validity of the OCB scale moved from rxy = 0.917 to rxy = 0.947. The results of the data analysis showed that there was a very significant relationship between organizational climate and OCB as seen in the correlation value (r) of 0.728 with a significance of 0.000 (p <0.05). The results of the categorization analysis show that the OCB variable has an empirical average of 64.20, which means it is classified as very high. The organizational climate variable has an empirical average of 83.83, which means it is classified as very high. The effective contribution of organizational climate to OCB is 53%, the remaining 47% is influenced by other factors outside the organizational climate.